Higher education and human capital re/thinking the doctorate in America - Callejo-Pérez, David M. 1972-; Fain, Stephen M. 1940-; Slater, Judith J.; SpringerLink (Online service). (Rotterdam SensePublishers, 2011)
This book attempts to re-imagine the purpose of the doctorate, which has historically been used to prepare leaders who will work to improve the sciences (social and physical), humanities, and professions, while articulating curriculum as a living shape where students, faculty, and institution melded in a humanist and creative process. This idea, seriously eroded by the explosion in doctoral degrees between the early 1970s (20,000 doctorate per year) and last year (to over 46,000)-and an explosion in doctoral and research universities that has created a crossroads for the doctorate in America. We believe the value of a doctorate is Intellectual Capital, and are particularly interested in encouraging reflection as an important characteristic of a successful quality doctoral program. We posit that a 'good doctoral' experience fosters active engagement in reflection on all elements of our work-the intellectual, advisory, and pedagogical work of faculty, curricular opportunities, as well as the intellectual of the doctoral candidates through an avocation that drives research and theory in our fields. Specific issues raised in this edited volume include comprehensive analysis of programs, rethinking evaluation and programmatic coherence, doctoral degrees beyond the discipline, subject, and field, and implications of individual identity. Along with authors' chapters, we paid attention to encourage reflection as an important characteristic of a quality doctoral program; positing that 'good doctoral' experiences foster active engagement in reflection on all elements of the doctoral experience, including program and curricular issues, personal relationships, work, and the creation of a community of scholars
Introduction: The doctorate and cultural capital Creating comprehensive educational experiences for the 21st century Ph. D. Monica F. Cox, Stephanie G. Adams, and Ingrid St. Omer The intensification of the professoriate : pedagogical casualties in an era of "prestige-seeking universities" Donna Adair Breault Re/thinking research training : scientific productivity as the beginning of a life program Luis Mauricio Rodríguez-Salazar and Carmen Patricia Rosas-Colin Four priorities for doctoral programs in small colleges/universities : a reflective essay Martha Combs and J. Randall Koetting Consolidating doctoral degrees : it makes sense M.O. Thirunarayanan Knowledge management as an approach to evaluation of advanced graduate programs Sebastían R. Díaz The EDD V2.0 : imagining a new doctorate in education William L. White and Jason Grinnell The new "proposed" doctoral degree in educational leadership (ED. D.) at a comprehensive university in Southern California Anthony H. Normore and Lynne H. Cook Complexity and uncertainty as drivers for a Ph. D. in mathematics education and science education Robert Mayes, Patricia McClurg, and Timothy F. Slater Doctoral programs in special education : what can we do to recruit culturally and linguistically diverse students? Diane Rodríguez and Kenneth Luterbach Individual doctoral education experiences and academic stewardship Meadow Graham, Sarah Selmer, and Erin Goodykoontz Negotiating the tenure-track journey : the competing and contesting discourse associated with becoming an academic Andrew T. Kemp, Joseph Flynn, and Samara Madrid Rethinking the doctorate from a liberal arts college Pablo Toral Doctoral study : a view from a veteran of advanced study wars Janice Sandiford Re-defining the meaning of impact Joshua J. Ode
Includes bibliographical references
Electronic reproduction
Keywords: Universities and colleges -- United States -- Graduate work; Doctoral students -- United States